Spinal motor atrophy in a floppy infant: a case report - Bainade, Kapil S.; Kotrashetti, Veeranna; Sonawane, Vijay B.; Agarwal, Rajdeep (International Journal of Contemporary Pediatrics, 2022)
Spinal muscular atrophy (SMA) is a progressive neuromuscular condition typically due to homozygous absence of the survival motor neuron gene (SMN1). It is characterized by progressive muscle weakness that limits motor development. Muscle weakness is associated with muscle atrophy and hypotonia, absence or marked decrease of deep tendon reflexes. Proximal muscles are more affected than distal muscles. Contractures and spinal deformity are a common impairment. Child with SMA gradually lose function over time. Electromyelography (EMG) and nerve conduction velocity shows anterior horn cells abnormality. No specific medical management is available for children with SMA. Interventions are usually supportive and may include physical therapy, occupational therapy, speech therapy, nutrition, orthotic management and possible surgery. This case report was of a 4 and half month-old female child with paucity of movement of lower limb since birth along with developmental delay.